Evaluacion de la eficaia de algunos plaguicidas sobre el acaro del ajo, Petrobia latens Muller (Acarina: Tetranychidae) - Del Estal, P.=700 1 Viñuela, E.; Jacas, J.; Marco, V.; Adan, A.; Budia, F.
(Es, En)
ilus., 10 ref.
Keywords: PETRONIA ACARINA; AJO; PLAGUICIDAS; ESPAÑA